Pengukuran Gaya Model Airfoil Sd7043 Didalam Terowongan Eswt (Education Small Wind Tunnel) - Yopiandi, Algeri; Harahap, Hanni Defianti; Anuar, Kaspul (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Airfoil or aerofoils that create a reaction force along the cross-section of the wings. This reaction force will make the aircraft able to fly at a certain flying speed. In engineering, there are different types of airfoils with different style characteristics as the airfoil geometry changes, which determines the usefulness of the wings of the aircraft. Therefore, it is necessary to conduct arodynamic testing to obtain the characteristics of an airfoil that is using a wind tunnel by making a cross-section of airfoils as a model to be engineered like the working state of the real airfoil. In this test, the airfoil used was Airfoil Low reynolds SD7043 with a chord ratio of 3 to span length. The testing stage was done by airfoil simulation on XFLR5 software with a range of 50,000 - 300,000 reynolds and then experimental testing was carried out using an open circuit wind tunnel, ESWT ( Education Small Wind tunnel) located in BBTA3 with an airflow speed of 4.87 m/s, 12.22 m/s, and 14.33 m/s. Test results at airflow speeds of 4.87 m/s were obtained graphs of experiment results that tended to stall faster than simulations due to the smoothness of the airfoil surface and the level of flow turbulence in the high test section at low air speeds.  At 12.22 m/s, there is a difference in chart trends in the post stall section where the ride begins to vibrate at an angle of attack of 12°. Then at a flow speed of 14.33 m/s the resulting data was obtained invalid because the accused model touched the wall of the test section. But from the overall data shows a curve trend similar to theoretical so it can be stated that the contour of the model airfoil SD7043. Keywords: Airfoil, Low Reynolds, SD7043, ESWT.